Prenos in obdelava scintigrafskih podatkov na računskem centru (RRC) s pomočjo laboratorijskega miniračunalnika - Cerar, Janez (Radiologia Iugoslavica, 1979)
A procedure for storage, handling and retrieval of large amount of data (1000 or more records), originating from a nuclear medicine lab is described. Most attention is paid to the selection of records from a fastacces disc-resident file.
Keywords: baza podatkov; computer science; information retrieval; information storage; medicina; nuclear-medicine data; povezava računalnikov; računalništvo